Analysis and experiment of centrifugal force for microfluidic ELISA CD platform - Ibrahim, F.; Jahanshahi, P.; Abd Rahman, N.; Abdul Kahar, M.K.B.; Madou, M.; Nozari, A.A.; Soin, N.; Md Dawal, S.Z.; Abi Samra, K. (2010)
This paper presents an analysis and experiment of centrifugal force for microfluidic Enzyme-Linked Immunosorbent Assay (ELISA) on a compact-disc (CD) platform. The ELISA CD was designed based on the centrifugal force as a driving force while capillary force acts as preventing barrier. The CD composed of 2 layers: the substrate layer is made of PMMA and the top layer is laminated with an Adhesive Sealing Films (ASF) or thermal seal. The PMMA substrate was fabricated by CNC micromachining. The ELISA CD consists of 7 reservoirs: waste, detection, serum, conjugate, washing solution, substrate and stopping solution. In the experiment, the reservoirs were filled with colour liquid and the fluid flow behaviour of the liquid in the CD was studied and monitored by a customized CD spin stand system equipped with visualization system. The experimental test results show an average of 9 error when compared with the theoretical calculation of burst frequency for all the reservoirs. Â© 2010 IEEE.